Sacredness as a Resource, Sacralization as a Strategy: Field Marshal Mannerheim and Finnish Fields of Media and Cultural Production - Jere Kyyrö (Equinox Publishing Limited, 2025)
This article re-thinks the concept of sacred in terms of sacralization, or as strategic action in a certain field of possibilities, and as sacredness, or as a resource to be appropriated in strategic action, aiming to accumulate or exchange specific capitals. Secondly, it looks into national symbols and their uses in the field of cultural production, especially the media in terms of sacralization and sacredness. Its Empirical data consists of media discussions around artworks re-interpreting Field Marshal Carl Gustaf Emil Mannerheim (1867– 1951) as a Finnish national symbol in the 2000s and 2010s. The dynamics of the field of cultural production and media affect the way Mannerheim is re-interpreted, and how these re-interpretations are received. Mannerheim as a sacred symbol can be used in many ways to accumulate specific capitals in the field of cultural production.